LEGAL POWERS OF CITIZENS' SELF-GOVERNMENT BODIES IN ENVIRONMENTAL PROTECTION IN UZBEKISTAN (Web of Teachers: Inderscience Research, 2025)
The article analyzes the problems of increasing the role of local governments in the implementation of the powers of citizens' self-government bodies in the field of environmental protection.